Tracking Solar Concentrators A Low Budget Solution - Jagoo, Zafrullah; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
Harnessing a multitude of complementary green energy sources is the only plausible way to satisfy the energy demands of a greedy global economy. The potential of solar energy (being the most abundant) in fulfilling part of the energy requirements of mankind is immense and constitutes the focal point of this book. A self-powered solar tracker that points directly towards the sun by means of an integrated control mechanism with two degrees of rotational freedom was studied and developed. The electro-mechanical control system is based on a precisely-timed microcontroller circuit that first computes the altitude and azimuth of the sun in real-time and then drives a pair of stepper motors that steer the solar tracker towards it. A locally built fibre-glass parabolic dish, the surface of which is lined with a reflective vinyl mirror film, serves to concentrate solar rays on its surface.
Introduction -- The Physics of the Sun -- Solar Tracking -- Solar Concentrators -- Experimental Results -- Conclusion -- Appendices.
Keywords: Energy; Renewable energy resources; Energy harvesting; Renewable energy sources; Alternate energy sources; Green energy industries; Energy; Renewable and Green Energy; Energy Harvesting; Electronic books